Between books and memories: the web as a place of nostalgia for the Círculo do Livro (Tempo e Argumento, 2021)
This work aims to understand the memory tracks of the Círculo do Livro on the web. This books sales club operated from 1973 to late 1990s, reaching 800 thousand members. Nowadays, in the digital space, former subscribers and interested people share memories and experiences, creating a space instigated by individual and collective memories. We believe, therefore, that blogs, websites and social networks have the potential to be characterized as “places of memory” for this book club, based on the concept of Pierre Nora (1993). To reflect on the theme, we will turn to authors who discuss concepts of memory, history and nostalgia, such Pierre Nora (1993), Andreas Huyssen (2000), Michael Pollak (1989), Maurice Halbwachs (1990) Svetlana Boym (2017) and Katharina Niemeyer (2019). As a methodology, we will carry out a survey of the results of the keyword Círculo do Livro on the online search site Google and we will use the methodology of Content Analysis, by Laurence Bardin (2011), to understand which are the main memorialistic and nostalgic narratives present in the selected articles and in the respective comments in each publication. We believe that, in addition to being a place of memory, the spaces for discussion about the Círculo do Livro in the digital environment also have the potential to be “places of nostalgia”, as the memory shared there is full of nostalgia and affection.Keywords: memory; place of nostalgia; web; digital; book clubs.